MENGEKSPLORASI STRATEGI DOSEN UNTUK MELIBATKAN MAHASISWA PERGURUAN TINGGI BERBASIS ISLAM DALAM PEMBELAJARAN DWIBAHASA - Khittotun Nahidin (Mastery: Master of English Language Journal, 2024)
Bilingual learning has become increasingly significant within contemporary educational discourse, responding to the growing demand for linguistic diversity and global connectivity. The purpose of this study is to analyze strategies that employed by lecturer to captivate and involve Islamic-based higher education students in bilingual learning environments. Through qualitative research methods by using in-depth interviews and observations, this study explores the diverse lecturer’s strategies to foster meaningful engagement and comprehension in both languages. The subject of this study is non-English lecturer who taught fifth semester students of English Department at STIT Miftahul Midad Lumajang. The research findings highlight the significance of interactive and participatory activities, scaffolding techniques, and the creation of inclusive learning environments in promoting active learning and linguistic proficiency among students. This research contributes to the existing literature on bilingual education by providing insights into lecturer’s strategies and offering practical recommendations for enhancing bilingual learning initiatives in Islamic-based higher education institutions.